2022
DOI: 10.35445/alishlah.v13i3.1125
|View full text |Cite
|
Sign up to set email alerts
|

Merdeka Belajar Kampus Merdeka: Application in Education Faculty

Abstract: The independence policy is a hot topic in the world of education. The premise that learning exists is carried out in the preparation of university graduates, both public and private, to meet the modern-day and rapid change challenges. Independent learning is a notion that aspires to excel from graduates as future leaders with an increasing number of personalities. Independent programs provide students with independence and flexibility to develop their potential through their hobbies and talents. This study wil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…The importance of the activities and results of the implementation of the MBKM program is the government's attention and this program is ogled by researchers with various previous studies (Astuti et al, 2022;Endrawan et al, 2021;Fuadi & Irdalisa, 2022;Sopiansyah & Masruroh, 2021) and this research is different from previous research, this research explains the readiness and reliability as well as the obstacles of the heads of study programs, secretary of study programs, and the dean of Bhayangkara University in realizing the MBKM. Therefore, it is important to research this research in order to know the role of the leadership of Bhayangkara University in realizing the success of MBKM.…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…The importance of the activities and results of the implementation of the MBKM program is the government's attention and this program is ogled by researchers with various previous studies (Astuti et al, 2022;Endrawan et al, 2021;Fuadi & Irdalisa, 2022;Sopiansyah & Masruroh, 2021) and this research is different from previous research, this research explains the readiness and reliability as well as the obstacles of the heads of study programs, secretary of study programs, and the dean of Bhayangkara University in realizing the MBKM. Therefore, it is important to research this research in order to know the role of the leadership of Bhayangkara University in realizing the success of MBKM.…”
Section: Introductionmentioning
confidence: 78%
“…(MBKM) program launched by the Minister of Education, Culture, Research, and Technology, Nadiem Makarin. MBKM is one of the innovations in educational programs in higher education (Fuadi & Irdalisa, 2022), either public or private. The program offers students the freedom to add experiences outside of their study program to improve the quality of learning for students.…”
Section: Introductionmentioning
confidence: 99%
“…In recent times, a lot of studies regarding Kurikulum Merdeka have been carried out. Several studies focused on the implementation of Kurikulum Merdeka were carried out by Hasim (2020), Fuadi & Irdalisa (2021), Inayati (2022), Sartini & Mulyono (2022), , Restu et al, (2022), Rizki & Fahkrunisa (2022), Fitriyah & Wardani (2022, Jusuf & Sobari (2022) the next revealed that the implementation at several elementary schools, sekolah penggerak, vocational school, and the university went well. Furthermore, the results of the study have been stated by Evy Ramadina (2021) and Arumsari & Koesdyantho (2021), the role of the principal has a strategic role in the process of progressing a Kurikulum Merdeka to advance the learning process centered on students and gives independence to work for educators and education personnel.…”
Section: Introductionmentioning
confidence: 99%
“…The annual decline in science literacy (Ni"mah, 2019) calls for a strategic solution by the Indonesian government. Through the Merdeka Belajar policy, Indonesia aims to compete in international education challenges (Yudhawasthi & Christiani, 2022) (Fernando et al, 2022) (Sampelolo & Kombong, 2022), aspiring to be a nation with high-quality education (Fuadi & Irdalisa, 2022). STEM education supports the development of science literacy skills.…”
Section: Introductionmentioning
confidence: 99%